Evolution of reception efficacy and execution in women`s volleyball according to level of competition - a descriptive study aged from 14-year-old to adult professional players - EcheverrÍa, C. J.; Ortega, E.; Palao, J. M. (Central European Journal of Sport Sciences and Medicine, 2019)
The aim of this study was to determine the technical performance profile of service reception with regard to execution and efficacy level according to level of competition in women`s volleyball. The sample of the study was composed of a total of 6,311 game phases from 187 sets in 48 matches played during season 2005-2006 by the following divisions: under-14, under-16, under-18, 2nd national senior division, 1st national senior division, and international senior division. The design of the study was a descriptive and inter- and intra-group correlational one. The variables studied included level of competition, technique used to serve, technique used to receive, zone where the reception was executed, and efficacy of reception. The results indicated that at higher levels of competition: a) there is higher efficacy in reception; b) number of errors decreases; and c) proportion of receptions that allow one or more attacking options for the receiving team increases. As level of competition increases, the effect of service on reception decreases, and receiving zones are more diverse. This study establishes the technical and tactical service-reception profiles in women`s volleyball, compares them, and establishes the dependence between variables to understand how the action changes throughout the levels of competition.